Correlative study of the cognitive impairment, regional cerebral blood flow, and electroencephalogram abnormalities in children with Down's Syndrome - Aydin, Mustafa; Kabakus, Nimet; Balci, Tansel Ansal; Ayar, Ahmet (Informa Healthcare, 2007)
The aim of this study was to investigate possible correlations of the cognitive impairment with abnormalities of regional cerebral blood flow and electroencephalogram in children with (Down's Syndrome) DS. Nine patients with DS were evaluated by single photon emission computed tomography (SPECT) in combination with clinical findings, electroencephalography (EEG), and magnetic resonance imaging (MRI). In cases with IQs below 40, there were one or more findings of abnormal EEG/MRI and brain perfusion SPECT. In 6 cases (66.7%) EEG findings were normal, but 3 (33.3%) had abnormal EEG findings. Perfusion abnormalities were most pronounced in the fronto-parieto-temporal region in the form of hypoperfusion (n = 5) and in the right hemisphere (n = 5) than the left hemisphere (n = 1). These findings suggest that the children with DS had varying levels of structural, perfusion, and electrophysiological abnormalities in the brain and these abnormalities were reflected by measurable alterations of the cognitive functions.
Keywords: cerebral perfusion; cognitive deficit; Down syndrome; SPECT; Tc-99m HMPAO